PENGUJIAN SIFAT MEKANIK DAN STRUKTUR MIKRO PADASAMBUNGAN PENGELASAN GESEK SAMA JENIS BAJA ST 60, SAMA JENIS AISI 201, DAN BEDA JENIS BAJA ST 60 DENGAN AISI 201 - Hermawan Widi Laksono; Sugiyanto Sugiyanto (JURNAL TEKNIK MESIN, 2017)
Direct friction welding is a welding material that is able to connect without the use of filler and have a good quality connection strength. This study was conducted to determine the friction welding process and the rotation to determine the quality of the connection with tensile testing, micro hardness and microstructure. The process is to do the similar of friction welding of steel ST 60 with 2.757 MPa friction pressure, upset pressure of 4.136 MPa with friction time 10 seconds and 3350 rpm rotational speed, friction welding similar AISI 201 with 3.447 MPa frition pressure, upset pressure of 4.136 MPa with friction time 10 seconds, rotational speed of 3350 rpm, and the dissimila of friction welding steel ST 60 and AISI 201 with a friction pressure of 3.447 MPa, upset pressure 4.136 MPa, friction time 10 seconds, and rotational speed of 3350 rpm. The results showed that when friction and compression force effect on the tensile strenght of friction welded joint. Highest tensile strenght at the similar steel ST 60 670.78 MPa, the similar friction welding of AISI 201 915.31 MPa and dissimilar of friction welding steel ST 60 with AISI 201 598.31 MPa. Micro hardness Vickers values in the weld area at the highest similar steel ST 60 243.8 HVN, the highest similar of weld area AISI 201 220.6 HVN, and on dissimilar of steel weld area ST 60 with AISI 201 593.4 HVN. While the grain boundary microstructure visible from the outside of the meeting to the center of the weld